(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Lavandula angustifolia Mill., commonly known as narrow-leaved lavender, is a perennial aromatic plant belonging to the Lamiaceae family. Its flowers and essential oil are widely used in the pharmaceutical, perfume, and folk medicine industries. This study investigates the effectiveness of vegetative propagation methods of lavender, focusing on cutting propagation and the influence of the growth regulator heteroauxin. The experiment was conducted in 2024–2025 under greenhouse conditions in Khiva district, Khorezm region. The results showed that the rooting rate of cuttings treated with heteroauxin solution reached 83%, while the control group achieved only 43%.